Hubungan Peran Suami dan Peran Petugas Kesehatan terhadap Pengetahuan Ibu Hamil tentang Baby Blues Syndrome di Puskesmas Lueng Bata Kota Banda Aceh - Siti Rahmah; Khaira Rizki; Nurul Sakdah (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Baby blues syndrome can have negative implications both in the short and long term, this has the potential to cause a tendency for passive attitudes in pregnant women, and result in neglect of the baby's needs, including a lack of attention and touch from the mother. This study aims to analyze the relationship between the contribution of husbands and the role of health workers with the level of understanding of pregnant women regarding Baby blues syndrome at the Lueng Bata Community Health Center, Banda Aceh. The study applied an analytical method with a cross-sectional approach, and involved all 73 pregnant women registered at the study location, with a total sampling technique. The data collection tool used was a questionnaire. The study took place from May 3 to 25, 2025. Based on the findings, there was a significant relationship between husband's support and pregnant women's knowledge regarding Baby blues syndrome (p = 0.001), and a significant relationship was also identified between the role of health workers on pregnant women's knowledge regarding the condition (p = 0.003). From the results obtained, it can be concluded that husband's support and the involvement of health workers mutually contribute to increasing pregnant women's understanding regarding Baby blues syndrome in the service area of ​​the Lueng Bata Community Health Center. It is recommended that health workers be more proactive in providing education and counseling regarding this syndrome so that pregnant women's knowledge regarding Baby blues syndrome can be maximized.